Strength Analysis on Horizontal Axis Wind Turbine Propeller Blade PVC Pipe with Angled Ends - Aji Tisa; Hangga Wicaksono; Bagus Wahyudi (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
The basic problem of appropriate wind energy technology is how to design wind turbines from materials that are easily available on the market, one solution is PVC pipe as the blade material. For this reason, it is necessary to analyze the working stress that occurs in the blade construction, so that the PVC pipe propeller wind turbine is safe when applied in society. The purpose of this study was to determine the effect of wind speed and tip elbow width on working stress. The simulation test method uses SolidWorks Flow Simulation Software and then the results are exported to Static Simulation to determine the strength of the material. Simulation tests were carried out with wind loads on PVC pipe propellers with wind speeds of 5 m/s, 6 m/s, and 7 m/s and elbow tip widths of 100 mm, 110 mm, and 130 mm. The results of the maximum stress value in the wind turbine simulation test with the addition of an elbow tip were obtained at a wind speed of 7 m/s and an elbow tip width of 130 mm